Regularities in the social network’s user distribution by the number of mutual contacts - Bakirov, Akhat; Suleimenov, Ibragim (Discoveries in Agriculture and Food Sciences, 2019)
This paper describes a study in which the pattern of distribution of the number of friends among users of the Vkontakte social network among residents of eight large cities of the CIS (Moscow, St. Petersburg, Almaty, Novosibirsk, Tashkent, Kiev, Yekaterinburg, Pavlodar) was studied. Experimental data show that this distribution is of a similar nature for all selected cities. A semi-empirical model was built, on the basis of which an explicit form of theoretical dependence was obtained, describing the nature of the distribution of the number of mutual contacts (“friends”) of users of social online networks. It is shown that this theoretical dependence agrees with satisfactory accuracy with experimental data for a sufficiently large sample of cities. It is established that the Dunbar number, which is included in the dependencies considered as a control parameter, is a characteristic of the communication environment of each specific city and correlates with the population of the city.